Rattus tanezumi ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
661. Oriental House Rat Rattus tanezumi French: Rat tanezumi / German: Asiatische Hausratte / Spanish: Rata caseraoriental Other common names: Oriental Rat, Oriental Roof Rat, Tanizumi Rat Taxonomy. Mus tanezumi Temminck, 1844, “japonais est Ta-nezumi.” Interpret- ed by J. K. Jones, Jr. and D. H. Johnson in 1965 as “Japan... vicinity of Nagasaki on the southern island of Kyushu.” Taxonomy of R. tanezum: and the entire R. rattus species complex (R. rattus and its relatives) is in flux, with possibly 4-6 distinct species in the R. rattus complex. As outlined under R. rattus, there are six main lineages within the R. rattus clade and four distinct species: R. rattus (Lineage I, 2n = 38), R. tanezumi (Lineage II, III and IV, 2n = 42 and 2n = 40 in Sri Lankan Lineage IV), R.sakeratensis (Lineage V), and R. tiomanicus (Lineage VI). Lineage II is the most widespread, probably originating in northern and western South-east Asia and southern China, Hainan, and Taiwan, spreading throughout China, Japan (including ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 831, DOI: 10.5281/zenodo.6887260 ...